2019
DOI: 10.1016/j.nuclphysb.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

k-essence f(R) gravity inflation

Abstract: solutions of the slow-roll theory, with regard to the scalar field. After that we employ two different approaches in order to study the phenomenological implications of the k-essence f (R) gravity theory. In the first approach, we choose the functional form of the f (R) gravity, and we investigate how the k-essence term affects the cosmological evolution in terms of the Hubble rate. After that we calculate in detail the slow-roll indices of the inflationary theory at hand, and correspondingly the observational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 59 publications
4
38
0
1
Order By: Relevance
“…Thus combining the present results with those of Ref. [10] which indicated compatibility of k-Essence f (R) gravity theory with the latest Planck data, this makes the theory particularly useful for describing inflationary dynamics. Let us focus in the case of having canonical scalar fields and matter domination cosmology, which is achieved by choosing c 1 = −1 and m = − 9 2 .…”
Section: A Stability and Viability Of The Equilibrium Pointssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus combining the present results with those of Ref. [10] which indicated compatibility of k-Essence f (R) gravity theory with the latest Planck data, this makes the theory particularly useful for describing inflationary dynamics. Let us focus in the case of having canonical scalar fields and matter domination cosmology, which is achieved by choosing c 1 = −1 and m = − 9 2 .…”
Section: A Stability and Viability Of The Equilibrium Pointssupporting
confidence: 83%
“…In Ref. [10] such a theoretical framework was given in terms of k-Essence f (R) gravity, and it was demonstrated that a viable inflationary era may be generated.…”
Section: Introductionmentioning
confidence: 99%
“…The first case corresponds to α >> 1, which makes the scalar field noncanonical per excellence. Many studies were carried out to refine the inflationary scenario within the framework of scalar fields possessing a noncanonical kinetic term [16][17][18][19][20][21][22][23]. In actuality, such kinematically-induced inflationary scenarios go back to the Starobinsky model [24,25] more than four decades ago, which considered a geometrical modification to general relativity in order to explain inflation.…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of f (R) gravity the dynamical behavior of the matter field and dark energy has been studied [41][42][43][44]. From the viewpoint of cosmology, many researchers have been carried out their studies from different directions [45][46][47][48][49][50][51][52][53][54][55][56][57][58]. A spherically symmetric vacuum BH solution in f (R) gravity has been derived in [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%